SHAP Parameter Sensitivity Analysis of Rock Mechanics Parameters - Dong, Lei; Wang, Longfei (International Journal of Computer Science and Information Technology, 2026)
Accurate determination of the rock mass's mechanical parameters directly affects engineering projects' safety and cost-effectiveness. Based on an extensive literature review, a dataset containing 318 sets of rock mass parameters is compiled to support our research. Key rock-mass descriptors—Q, RMR, GSI, UCS, the rock material constant m_i, and the disturbance factor D—are first standardized to mitigate scale effects. A correlation-coefficient matrix is then computed and visualized with a heatmap to quantify inter-variable relationships. The results indicate a strong positive correlation between Q and RMR and a moderate negative correlation between m_i and D. Some mechanical variables show near-unity positive correlations with indicators such as RMR and UCS, suggesting highly consistent trends. Pairwise distribution analyses further reveal an approximately linear relationship between GSI and RMR, a logarithmic tendency between Q and RMR, and clustered patterns in the m_i–D space, implying potential multicollinearity and nonlinear interactions.